2006
DOI: 10.1177/1078087406291444
|View full text |Cite
|
Sign up to set email alerts
|

Shaming the Inside Game

Abstract: Liberal expansionism is the dominant approach to addressing the problems of American cities. This approach combines liberal political philosophy with the idea that these problems can be solved only by creating linkages between cities and resources beyond their boundaries. The case for liberal expansionism derives from the shaming of the inside game-a critique of community development and the progressive capacities of cities themselves. I develop a countercritique of this notion. I find that much of it is unjus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(3 citation statements)
references
References 44 publications
0
3
0
Order By: Relevance
“…Just as SSGI found a critic in Ostrom, UAR played host to David Imbroscio's critique of the "liberal expansionism" that lay at the center of the regionalist paradigm (Imbroscio 2006). Like Ostrom, Imbroscio identified regionalism's key propositions and drew on the available empirical evidence, as well as urban theory (contra Ostrom), to argue that the underpinnings of liberal expansionism are highly questionable.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Just as SSGI found a critic in Ostrom, UAR played host to David Imbroscio's critique of the "liberal expansionism" that lay at the center of the regionalist paradigm (Imbroscio 2006). Like Ostrom, Imbroscio identified regionalism's key propositions and drew on the available empirical evidence, as well as urban theory (contra Ostrom), to argue that the underpinnings of liberal expansionism are highly questionable.…”
mentioning
confidence: 99%
“…Like Ostrom, Imbroscio identified regionalism's key propositions and drew on the available empirical evidence, as well as urban theory (contra Ostrom), to argue that the underpinnings of liberal expansionism are highly questionable. Moreover, Imbroscio maintains that such perspectives blithely ignore “literally thousands of alternative local economic institutions capable of anchoring capital (such as worker-owned firms), of generating alternative revenue streams for cities (such as municipal ownership), and of augmenting the degree to which local economies benefit from local economic activity (via enhancing local multipliers)” (Imbroscio 2006, 243; also see, Guinan and O’Neill 2020). Imbroscio's key point was that the path to urban prosperity and equality was not via institutional fixes but through the development of locally rooted alternative economic arrangements, a point Schragger would amplify forcefully in his book, City Power (Schragger 2016).…”
mentioning
confidence: 99%
“…First, the theory of spatial mismatch and empirical finding indicated that poverty was positively related to the lack of physical accessibility to economic opportunities (Holzer, 1991). Since housing mobility programs could bridge the gap between low-skilled workers and low-skilled jobs in suburbs, housing mobility programs were considered the best solution to fight poverty by many urban scholars (Imbroscio, 2004b(Imbroscio, , 2006.…”
Section: Program Theories Of Housing Mobility Programsmentioning
confidence: 99%